“He stopped to lower his window and say hello”: Jonathan Franzen, Neorealism and De-politicized Communitarianism - Aleksandra Zuzanna Leniarska (European Journal of American Studies)
Referencing the term “Great American Novel,” the August 2010 cover of Time Magazine introduced Jonathan Franzen as “the Great American Novelist,” a change that draws attention to the persona of the author, as well as to his alleged ability to capture the American experience in the 21st century. Based on the analysis of Franzen’s novels, this article describes changes in mainstream American fiction under neoliberalism—the shift towards strong authorial presence, omniscient narrator, mimetism, middle-class family saga—that arguably constitute a post-postmodernist tendency, neorealism. In spite of Franzen’s extra-literary promise of political critique of neoliberalism and cultural critique of therapy discourse, his fiction in fact performs de-politization on narrative level. Happy endings exemplify a new model of success attained by characters who renounce their idealism—happiness based on small community, family, and abandonment of the hope for a structural change. This redefinition of success is presented as anti-establishment, and is combined with a style of writing that stresses verisimilitude and pretends neutrality, while applying strong narratorial authority. Those inconsistencies between the declarative and narrative levels can themselves be perceived as an intervention of neoliberalism in literature, as they cater to the demand for political discontent from Franzen’s liberal, intellectual readership, while affectively soothing it with de-politicized happy endings.